Erosão dentária em crianças diagnosticadas com a doença do refluxo gastroesofágico - Patricia Alves Drummond de Oliveira (2011)
Dental erosion (DE) is a progressive and irreversible loss of dental hard tissue by acid dissolution not associated with bacteria. The gastroesophageal reflux disease (GERD) is considered one of the intrinsic factors associated with dental erosion, because the stomach acid pH that returns to the oral cavity is below the critical pH for enamel dissolution. This study evaluated the occurrence of dental erosion and its association with diet, oral hygiene, medical history and socio-demographics characteristics of 43 pediatric patients with ages from 2 to 14 years-old at Hospital das Clinicas, UFMG in Belo Horizonte, Minas Gerais who were diagnosed with gastroesophageal reflux disease by the 24 hour pH monitoring. Clinical examination was performed at the Hospital, using the index of O'Sullivan. The researcher was previously calibrated by an experienced examiner in the use of the index (inter-examiner kappa: 0.90 and intra-examiner: 0.95). A questionnaire was completed by the parents with information about the socio-demographic characteristics of the family, as well as information about medical history, dietary and oral hygiene habits and health of children, with the purpose of relating this information to erosion experience. The data were analyzed using the Statistical Package for Social Sciences (SPSS version 17.0), and by the Chi-square and Poisson Regression, with a significance level of 5%. Variables with p<0.20 in univariate analysis were included in the regression model. This study was approved by the Ethics in Research Committee Federal University of Minas Gerais (ETIC 0117.0.203.000-10) and the Board of Education and Research from Hospital of UFMG (039/10). DE was found in 25.6% of children. The most affected surfaces were the palatal and incisal (62.1% of cases). Socio-demographic and dietary habits were not associated with experience of dental erosion. Univariate analysis showed a statistically significant association between the type of toothpaste used and the occurrence of erosion, which was higher among children who used toothpaste for adults (p = 0.039). Children who used medication for asthma had greater experience of erosion. Although this association was not statistically significant in univariate analysis (p = 0.08), it was considered in multivariate analysis. In the regression model these two factors were significantly associated with the presence of erosion (PR 4.98, 1.34 to 18.51 and RP 3.65, 1.24 to 10.70, respectively). These results demonstrate that a significant proportion of children with gastroesophageal reflux had dental erosion which was associated with use of adult toothpaste and the use of asthma medicine.